Poezja w epoce cyfrowej - Jedrzejewski, Franck (Postscriptum Polonistyczne, 2020)
Interview with Jacquese Donguy, a French poet, performer, translator and literary critic, professor at the University of Paris, on experimental poetry in the digital world.